Hepatocyte-Specific SR-BI Gene Transfer Corrects Cardiac Dysfunction in Scarb1-Deficient Mice and Improves Pressure Overload-Induced Cardiomyopathy. Issue 9 (September 2018) - Muthuramu, Ilayaraja; Amin, Ruhul; Aboumsallem, Joseph Pierre; Mishra, Mudit; Robinson, Emma Louise; De Geest, Bart
Abstract : Objective—: We investigated the hypothesis that HDL (high-density lipoprotein) dysfunction in Scarb1 −/− mice negatively affects cardiac function both in the absence and in the presence of pressure overload. Second, we evaluated whether normalization of HDL metabolism in Scarb1 −/− mice by hepatocyte-specific SR-BI (scavenger receptor class B, type I) expression after E1E3E4-deleted adenoviral AdSR-BI (E1E3E4-deleted adenoviral vector expressing SR-BI protein in hepatocytes) transfer abrogates the effects of total body SR-BI deficiency on cardiac structure and function. Approach and Results—: Transverse aortic constriction (TAC) or sham operation was performed at the age of 14 weeks, 2 weeks after saline injection or after gene transfer with AdSR-BI or with the control vector Adnull. Mortality rate in Scarb1 −/− TAC mice was significantly increased compared with wild-type TAC mice during 8 weeks of follow-up (hazard ratio, 2.02; 95% CI, 1.14–3.61). Hepatocyte-specific SR-BI gene transfer performed 2 weeks before induction of pressure overload by TAC potently reduced mortality in Scarb1 −/− mice (hazard ratio, 0.329; 95% CI, 0.180–0.600). Hepatocyte-specific SR-BI expression abrogated increased cardiac hypertrophy and lung congestion and counteracted increased myocardial apoptosis and interstitial and perivascular fibrosis in Scarb1 −/− TAC mice. Scarb1 −/− sham mice were, notwithstanding the absence of detectable structural heart disease, characterized by systolic and diastolic dysfunction and hypotension, which were completely counteracted by AdSR-BI transfer. Furthermore, AdSR-BI transfer abrogated increased end-diastolic pressure and diastolic dysfunction in Scarb1 −/− TAC mice. Increased oxidative stress and reduced antioxidant defense systems in Scarb1 −/− mice were rescued by AdSR-BI transfer. Conclusions—: The detrimental effects of SR-BI deficiency on cardiac structure and function are nullified by hepatocyte-specific SR-BI transfer, which restores HDL metabolism. Abstract : Supplemental Digital Content is available in the text.